Shape optimization of reticulated shells with constraints on member instabilities. Issue 9 (2nd September 2019) - Zhao, Zhongwei; Wu, Jinjia; Liu, Haiqing; Liang, Bing; Zhang, Ni
ABSTRACT: Reticulated shell structures are commonly adopted because of their large spanning capacity and novel appearance. These structures generally comprise slender beam members, which may cause the buckling of entire structures. A shape-finding method is proposed in this study to eliminate the bending moment while optimizing the member buckling capacity of reticulated shell structures. The bending stiffness of connections can be accurately considered in the topology optimization analysis. This study can systematically be adopted for designing, analysing and optimizing such structures. All of the work presented was conducted using a general finite element analysis program and can be easily mastered by engineering designers while avoiding tedious programming work.